Modelo conceptual de la participación de las Pymes mexicanas en el Capitalismo de Stakeholders en la era post-COVID19 - Esparza-Rodriguez, Saul Alfonso; Esquivel Fernández, Enrique; Chavez Gallegos, Glenda Marisa; Garcia Tapia, Gabino; Raziel Rodríguez, Paulo (Revista del Centro de Investigación de la Universidad la Salle, 2024)
The crisis caused by COVID-19 was an event experienced globally and simultaneously, generating changes in the way people work, study, and carry out their social activities, giving the beginning of practical and theoretical conversations about the need to design and implement a new model of capitalism, oriented to the management of interest groups. The present work presents the theoretical and conceptual review related to the theoretical and conceptual constructs related to the contribution to the planet, people management, prosperity orientation, and governance factors that explain the participation of Mexican SMEs in interest group capitalism. Thus, it is shown that the process of adaptation to a "new normality" scenario will represent a factor of fundamental importance for social coexistence considering the risk represented by the effects caused by the new coronavirus, through the development of emerging strategies characterized by promoting the Adequate interaction between interested parties that constitute a model of capitalism that must equally weigh the social, economic, environmental and health dimensions for society in the long-term.